Studi Analitis dan Eksperimental Mekanisme Slip-Kritis Sambungan Struktural Baut Baja - Noek Sulandari; Yosafat Aji Pranata; Anang Kristianto (Universitas Kristen Maranatha, 2023)
Indonesia's geographical location makes Indonesia as a country prone to earthquake risks, both tectonic as well as volcanic. The Indonesian National Standard (SNI) 1729:2015 requires bolt connections for steel buildings with a height of more than 38 m must use high-strength bolts (HSB) with pre-tensioning. Snug-tight and pre-tensioned bolted connections are physically no different. Differences will occur when the connection is loaded, namely for pre-tensioned joints, where slip between the plates being joined as a result of the bolt hole size being larger than the bolt diameter will occur when the slip limit strength is exceeded. This study aims to observe the strength and behavior of pre-tensioned bolted joints with increasing loads. The analysis was carried out according to SNI 1729:2015, with data validation through experimental tests using BJ37 plate specimens loaded with concentric axial tension. The connection uses a HSB-A325 M12 standard hole with class A surface preparation. Pre-tension bolts are applied by turn-of-nut. The test results show that the strength of the slip limit (Pslip) is 37.998 kN; this value is 5.7% higher than the analytical result of 35.94 kN. After reaching the slip limit strength, the connection can still accept the load with the bearing force transfer mechanism and reach the connection limit strength (Pu) of 50.197 kN, 32% exceeding the slip limit strength. Turn-of-nut, one of the methods recommended by SNI 1729:2015, is a fairly simple method for pre-tensioning because no special additional tools are required and the required minimum pre-tensioning force can be met by achieving Pslip experimental results not lower than the results of the analysis.